Tradisi Nyeeb Dalam Upacara Perkawinan Di Desa Tajun, Kecamatan Kubutambahan, Kabupaten Buleleng (Kajian Filosofi Hindu) - Putu Eka Arsadi; I Wayan Gata; I Wayan Titra Gunawijaya (Vidya Darsan: Jurnal Mahasiswa Filsafat Hindu, 2022)
The Nyeeb tradition is a tradition as a marriage continuation ceremony in Tajun Village and is believed to have extraordinary meaning. Based on this background, the following problems are formulated: 1) What is the form of the Nyeeb tradition in the wedding ceremony in Tajun Village, Kubutambahan District, Buleleng Regency, 2) What is the function of the Nyeeb tradition in the wedding ceremony in Tajun Village, Kubutambahan District, Buleleng Regency, 3) What is the function of the Nyeeb tradition in the wedding ceremony? the philosophical meaning of the Nyeeb tradition in the wedding ceremony in Tajun Village, Kubutambahan District, Buleleng Regency. The functions of the Nyeeb tradition are: a function as cultural preservation, a social function, namely to improve community kinship and village manners, and a togetherness function, which is seen when the Tajun Ngayah Village community prepares ceremonial facilities and infrastructure from the beginning of the activity until the end of the Nyeeb tradition together. -same. The philosophical meanings contained in the Nyeeb tradition are: the meaning of purification which is to purify the husband and wife who will become new manners in addition to purifying the kama bang and kama petak to give birth to offspring of suputra and suputri, the symbolic meaning contained is found in the offerings of devotion sorohan Nyeeb, The meaning of harmony in the Nyeeb tradition, namely the harmonious relationship between humans and Hyang Widhi Wasa can be seen from the matur piuning procession, human relations with fellow humans can be seen from Nyeeb participants with the manners of the traditional village where they mingle and communicate with each other, and the harmonious relationship between humans and their environment can be seen from the procession of gathering and cleaning the environment around the implementation of the Nyeeb tradition.